Strengthening Culture Work in Improving Professional Performance Primary School Teachers - Rochaendi, Endi; Ma'mun, Saeful; Mahfud, Mahfud (IJCAR: Indonesian Journal of Classroom Action Research, 2024)
Literacy studies aim to build a strengthening model framework culture. Work in upgrading the performance profession of elementary school teachers who can push change the attitudes and behaviour of teachers. Study results describe that in strengthening culture work, there are three important elements: values, system work, source power man, and participating environment, as well as influential elements in strengthening culture work. Structuring culture works in the enhancement of performance. The profession of an elementary school teacher is an effort to develop moral and cultural values, productive work, improve perception, patterns, thoughts and behaviour of teachers in operating tasks, principles and functions, as well as increase the performance of teachers to be more skilled and creative as well as dynamic for repair its performance in a way sustainable so that can increase service and power competitive in work and act. In relationships, it can be confirmed that culture work is closely related to behaviour in finished work. In the context of strengthening culture work in upgrade performance, the profession of an elementary school teacher is implemented through three stages that are stage awareness, stage capacity, and stage empowerment, which in turn focuses on the effort to create orientation of excellent service, accountable, competent, harmonious, loyal, adaptive and collaborative in build and improve management processes education in the unit education.